Efficiency evaluation of grant policy in sport by principles of program financing - Vladimír Hobza; Jiří Skoumal (Palacký University Olomouc, 2010)
The paper concerns with mutual interconnection of goals of municipal development concepts and methods of their assessment. Based on grant policy of selected municipalities (regions, communities) and on the principles of program financing, a specific method of evaluation performance is suggested, which enables to evaluate closer control of sport development, visions, proclaimed goals and sport support programs. The principle of the proposed procedure is based on the use of indicators and methods: CEA, CBA, CUA and CMA in program financing of sport - a field where it is not possible to calculate only direct economic results but it is necessary to consider the impact of externalities (benefits). The authors suggest procedures, which lead to a higher level of control, transparency and efficiency of public spending in the municipal sphere. The goal of this contribution is to point out possible means of assessing grant proposals, as a support tool for decision-making and subsequent control.